AMALAN TERBAIK KEPIMPINAN PENGETUA SEKOLAH YANG BERJAYA DARI PROJEK ‘ISSPP’ : SATU TINJAUAN - Abd Paris Khan, Siti Shamizatulfiza; Abdul Razzaq, Abdul Rasid (Online Journal for TVET Practitioners, 2018)
Many daily underperformed secondary schools in Malaysia were able to arise and done numerous improvement and crafted fame in various fields. However, the success and experiences that the school principals had gone through were rarely known and documented, to be shared and made as a reference in the world of school leadership in Malaysia. The International Successful School Principalship Project (ISSPP)is a project carried out in more than 20 countries and involved more then 100 case studies pertaining to characteristics and the best practices applied by the principals who managed to change theirs schools and improved their students’ achievements. Research which was started by Gurr, Drysdale and Mulford in 2001 had involved different types of schools in the selected countries. The school leaders involved in this research were the one who were successfully lead their schools until the students obtained outstanding academic achievement, until the schools exhibited excellent reputation in the community and able to achieve excellent success in different fields. A few models of successful school leadership constructed from this project and could be a reference to principals in Malaysia. Therefore, this paper focuses on the best practices executed by two successful principals, to be exampled by the other principals so that they could also attain the same success and excellent in various fields.